Enhancing customer experience in information space through perception management strategy / Wan Abdul Hadi Wan Salleh - Wan Salleh, Wan Abdul Hadi (2012)
The scattered of information had give an industry difficulty to measures identify and resolve customer experience management issues. This study aims to assess the fundamental of customer perception management. Then customer perception management model will be examined in service industry particularly airlines. Interviews were conducted with customers and key business area personnel which currently having direct interaction with customer. At the same time, focus group has been conducted to obtain secondary data. Adapted from Five (5) Forces Competitive Model, the analysis has been performed to validate and assess the challenges in customer experience management. Using Case Study Research Method at Malaysia Airlines, a Customer Perception Strategy (CPS) is developed to evaluate disparate customer data, residing across many systems, builds experience profiles and suggests appropriate contextual actions where experience is poor. The strategy provides value in identifying issues, understanding them in the context of the overall Customer Experience and dealing with them appropriately. In this light, the research describes a strategic approach to the use of Information Systems as a means of improving Customer Experience.